Assessment of Tech-Enabled Property Management as an Efficient Modality for Effective Property Management in Awka, Anambra State - R. O., Sado; C. U., Jinanwa; C. B., Ndeche (International Journal of Real Estate, 2025)
This study employs a descriptive research design to comprehensively understand the adoption and impact of technology in property management, specifically in Awka, Anambra State, Nigeria. The study aims to assess Tech-enabled property management as an efficient modality to effective property management in Awka, Anambra State. The study draws on the Technology Acceptance Model (TAM) to understand users’ acceptance of technology, emphasizing perceived usefulness (PU) and perceived ease of use (PEOU). The investigation involved 100 respondents, comprising Estate Surveyors, tenants, and property managers, surveyed through a structured questionnaire— the Impact of Technology in Property Management (ITPM) questionnaire. Three research questions; how the integration of technology in property management impact the efficiency of routine tasks such as rent collection and maintenance? What extent does tech-enabled property management contribute to enhancing tenant experiences and overall satisfaction? And, what challenges are associated with adopting technology in property management within the Nigerian context? And corresponding hypotheses guided the study, Descriptive statistics (mean, percentage and frequency) were adopted in answering the research questions, while paired ample t-test, chi-square and regression analysis were used in angering the research hypotheses. Findings reveal that the integration of technology in property management in Awka significantly enhances efficiency and tenant satisfaction. However, challenges such as high initial costs and integration complexities demand thoughtful consideration during implementation. These findings serve as a foundation for future research and offer practical insights for property managers, tenants, and policymakers navigating the dynamic landscape of technology adoption in property management.